The potential of ethanol extract of white pomegranate leaves (Punica granatum L) as anti-bacterial - Susilawati, Ni Made; Arnawa, I Gede Putu; Octrisdey, Karol; Kambuno, Norma Tiku (Jurnal Teknologi Laboratorium, 2020)
Treatment of infections using penicillin-derived antibiotics such as methicillin has been found to cause antibiotic-resistant bacteria. This bacteria could produce a beta-lactamase enzyme to form a resistant strain. Research on antibacterial activity continues to develop. Pomegranate (Punica granatum L.) was one of the herbal plants whose fruit has long been used for the treatment and prevention of various diseases. This study aimed to determine the potential inhibition of white pomegranate leaf extracts (Punica granatum L.) on the growth of Gram-negative bacteria including Escherichia coli Extended-Spectrum Beta-Lactamase (ESBL) strain and Gram-positive bacteria Staphylococcus aureus Methicillin-Resistant Staphylococcus aureus (MRSA) strain. White pomegranate leaf extract macerated with ethanol 96%, evaporated to obtain pure extracts made with a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and with 100% tested with invitro diffusion method. It was found that the extract of white pomegranate leaves with 30% (10.00 Â± 0.0) concentration was able to inhibit the growth of positive Gram bacteria strains MRSA and the extract was unable to inhibit the growth of Escherichia coli bacteria strain ESBL.